2015
DOI: 10.1515/jccm-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arterial Thrombolysis in Second Trimester of Pregnancy. A Case Report

Abstract: Here we present a successful intra-arterial thrombolysis performed in the second trimester of pregnancy (21 weeks). The intervention resulted in complete recanalization of the occluded right middle cerebral artery and favourable clinical and gestational outcome. Together with cases described in respective medical literature our report affirms that in pregnancy acute ischemic stroke could be treated effectively applying intra-arterial thrombolysis (using rt-PA). This therapy could provide opportunity to help in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Our two pregnant patients with AIS showed short‐term improvement in functional status after receiving IV alteplase. This adds to most of the published case reports (n=27) with documented neurologic improvement and without fetal complications (Table ) . There are five case reports with negative outcomes in the mother, fetus, or both after the administration of alteplase .…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Our two pregnant patients with AIS showed short‐term improvement in functional status after receiving IV alteplase. This adds to most of the published case reports (n=27) with documented neurologic improvement and without fetal complications (Table ) . There are five case reports with negative outcomes in the mother, fetus, or both after the administration of alteplase .…”
Section: Discussionmentioning
confidence: 66%
“…Review of references identified an additional case report. 11 An additional six cases from four abstracts have been reported in abstract form only. [12][13][14][15] Review of abstracts from national meeting presentations identified national database reviews that significantly increased the overall number of reported cases, although individual patient demographics, presentations, interventions, and outcomes were not reported in these.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations